Ordinance no. 1, § 7, THE MINING ECHO, Jul. 7, 1877, at 1 - (:unkn) unknown (My University, 1870)
§Any person who shall discharge any gun, pistol, or other firearms, within the limits of this city, shall be deemed guilty of a misdemeanor, and upon conviction, be fined in a sum not less than $5.00 nor more than $20.
Keywords: DISCHARGE